Pemberian Infra Red dan Terapi Latihan pada Kasus Pasca Dislokasi Shoulder Sinistra - Ifa gerhanawati; Ainul Ghurri; Danuditya Purna Atmaja; Hafizah Sururul Nur Rakhmawati; Fransisca Xaveria Hargiani (Lembaga Pengembangan Kinerja Dosen, 2025)
Shoulder dislocation is a fairly common musculoskeletal injury, particularly in individuals who engage in high-impact physical activity or sports involving extreme shoulder joint movements, such as athletes. This condition can cause significant pain, limited range of motion (ROM), decreased muscle function, and impact daily functional activities. Physiotherapy plays a crucial role in the rehabilitation process after a shoulder dislocation, with the primary focus being on reducing pain, restoring ROM, improving muscle function, and preventing recurrence. This study aimed to evaluate the effectiveness of a combination of infrared therapy and isometric hold-relax exercises in reducing pain and increasing ROM in patients with left shoulder dislocation. The study design used a case study approach with a single patient as the subject. The physiotherapy intervention consisted of six phased and scheduled sessions. Infrared therapy was administered to help relax muscle tissue, improve local blood circulation, and reduce pain intensity. Meanwhile, isometric hold-relax exercises were applied to increase muscle flexibility, expand ROM, and restore shoulder joint function. Evaluations were conducted before and after the intervention, measuring pain levels using a subjective pain scale and assessing range of motion (ROM) using a goniometer. The results showed a significant reduction in pain and a significant increase in joint mobility after undergoing the physiotherapy program. These findings indicate that the combination of infrared therapy and isometric hold-relax exercises can be an effective method in shoulder dislocation rehabilitation, supporting functional recovery and potentially reducing the risk of re-injury. This study also emphasizes the importance of a multimodal therapeutic approach in the management of musculoskeletal injuries for optimal outcomes.